Physical activity of Ukrainian people interned in camps on the territory of the province of Łódź in the years 1920-1938 - Julian Jaroszewski (Jan Długosz University in Częstochowa, 2020)
After the truce between Poland and Russia had been signed in October 1920, the soldiers of the Ukrainian People's Republic who crossed the Polish border were first disarmed and then imprisoned in internment camps. In 1921 over 15 000 people were sent to camps on the territory of the province of Łódź, namely to Kalisz-Szczypiorno, Piotrków Trybunalski and Strzałkowo. The camps functioned until 1924 and after their liquidation, the internees had to leave the territory of Poland or, after obtaining the status of political immigrants, they were granted a permit to stay. Those who stayed settled in Kalisz, in the so-called Ukrainian Stanitsa. They lived in shabby conditions. However, although isolated and subjected to hostile agitation by Bolshevik authorities, they managed to restore their patriotic and national spirit as well as their sports and health character. Cultural and educational activity, apart from theatres, choirs, libraries, the press was run primarily by schools. The Ukrainian people attended both camp (Ukrainian) schools and Polish schools where they participated in PE classes as part of the curriculum. Moreover, the sports movement developed, supported by the American YMCA association. Their sports level made it possible to compete with the leading regional teams. Sports Activities, apart from their pro-health impact, integrated the Ukrainian community.